Comparison extraction of peanut skin between CO2 supercritical fluid extraction and soxhlet extraction in term of oil yield and catechin - Putra, N.R. (Universiti Putra Malaysia Press, 2018)
The objective of this study was to compare the extraction of peanut skin using supercritical carbon dioxide extraction and soxhlet extraction in terms of oil yield and catechin. For supercritical fluid extraction, the temperatures used were 40 and 70°C, while pressure used was 10 and 30 MPa, the flow rate was CO2 3 mL/min, and the concentration of co-solvents was 0 and 5. Meanwhile, for soxhlet extraction, the extraction time was 6 hr with ethanol, hexane and water as the solvents. The results showed that soxhlet extraction gave the highest yield of extract (36.282) using ethanol as solvent as compared with supercritical CO2 extraction (15.47) at pressure 30 MPa, temperature 70°C and 5 concentration of co-solvent. This study reveals that the extracts from SC-CO2 extraction yielded the highest amount of catechin (208.73 μg/g sample) compared with that yielded in the soxhlet extraction (42.24 73 μg/g sample) with distilled water as a solvent analysed with High Performance Liquid Chromatography (HPLC). © 2018 Universiti Putra Malaysia Press.